EXTRACTIVE SUBSTANCES OF SAPROTROPHIC MUSHROOMS: FLAMMULINA VELUTIPES, HYPHOLOMA CAPNOIDES, ARMILLARIA BOREALIS, ARMILLARIA CEPISTIPES. HEAVY METAL CONTENT - Bakanov, Vyacheslav Vadimovich; Vedernikov, Dmitriy Nikolaevich; Kruchina-Bogdanov, Igor Vadimovich; Eltsova, Liubov Sergeevna (Химия растительного сырья, 2022)
The article is concerned to the study and comparison of the extractive substances chemical composition of typical saprotrophic mushrooms that grow in the forests of St. Petersburg and the Leningrad region: Flammulina velutipes, Hypholoma capnoides, Armillaria borealis, Armillaria cepistipes. The article analyzed and compared the chemical composition of low-molecular compounds of caps and legs separately. The composition of heavy metals was compared: cadmium, mercury, iron. The content of heavy metals in the studied fungi was compared with those studied earlier (Lentinula edodes and Pholiota squarrosa). Cadmium and mercury are found mainly in the caps of autumn mushrooms. The composition of fatty acids, sterols, carbohydrates and sugar alcohols in various parts of mushrooms (stems and caps) was determined and compared. It was revealed that glycerin is presented in all types of mushrooms and is contained in large quantities in the stems and caps of F. velutipes. The qualitative composition of sugar alcohols is approximately the same in all mushrooms, but the quantitative composition has specific differences. Sugar alcohol threitol is contained in Armillaria.